Biomechanical design using in-vitro finite element modeling of distal femur fracture plates made from semi-rigid materials versus traditional metals for post-operative toe-touch weight-bearing. (January 2021) - Gee, Aaron; Bougherara, Habiba; Schemitsch, Emil H.; Zdero, Radovan
Highlights: This study designed new distal femur plates using semi-rigid materials. Hip load mimicked toe-touch weight-bearing right after femur fixation surgery. The design criterion was controlled axial interfragmentary motion for early healing. Stiffness, bone stress, implant stress, and interfragmentary motion were computed. Results were compared to traditional steel and titanium distal femur plates. Abstract: This proof-of-concept study designs distal femur fracture plates from semi-rigid materials vs. traditional metals for toe-touch weight-bearing recommended to patients immediately after surgery. The two-fold goal was to (a) reduce stress shielding (SS) by increasing cortical bone stress thereby reducing the risk of bone absorption and plate loosening, and (b) reduce delayed healing (DH) via early callus formation by optimizing axial interfragmentary motion (AIM). Finite element analysis was used to design semi-rigid plates whose elastic moduli E ensured plates permitted AIM of 0.2 - 1 mm for early callus formation. A low hip joint force of 700 N (i.e. 100% x body weight) was applied, which corresponds to a typical 140 N toe-touch foot-to-ground force (i.e. 20% x body weight) recommended to patients after surgery. Analysis was done using 2 screw materials (steel or titanium) and types (locked or non-locked). Steel and titanium plates were also analyzed. Semi-rigid plates (vs. metal plates) had lower overall femur/plate construct stiffnesses of 508 - 1482 N/mm, higher cortical bone stresses under the plate by 2.02x - 3.27x thereby reducing SS, and lower E values of 414 - 2302 MPa to permit AIM of 0.2 - 1 mm thereby reducing DH.